2016
DOI: 10.1002/mawe.201600462
|View full text |Cite
|
Sign up to set email alerts
|

Single‐walled carbon nanotubes affect the expression of the CCND2 gene in human U87 glioma cells

Abstract: The effect of single-walled carbon nanotubes (SWCNTs) on the expression level of several genes, related to cell cycle control, cell proliferation and migration in human glioma cell line U87 was investigated. The exposure of human U87 glioma cells to single-walled carbon nanotubes in different concentrations during 24 of 48 h affects the expression of CCND2 (Cyclin D2), DTNA (Dystrobrevin alpha), PARVB (parvin beta), DUSP1 (dual specificity phosphatase 1), PFKFB3 (6-phosphofructo-2-kinase/ fructose-2,6-bisphosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“…It has been shown that very low quantities of SWCNTs may significantly disturb the expression of microRNAs, which participate in the post-transcriptional regulation of most mRNAs and regulate variable physiological and pathophysiological processes in different cells and tissues, including brain tissue (Schratt et al 2006;Agarwal et al 2015;Matamala et al 2018;Wang et al 2018;Goldewski et al 2019;Krichevsky et al 2019;Ma et al 2019;Brennan and Henshall 2020). Previously we have shown that SWCNTs affect the expression of genes encoding enzymes and factors related to immune response, cell proliferation, and cell cycle control as well as some microRNAs in U87 glioma cells and normal human astrocytes (Minchenko et al 2016(Minchenko et al , 2018Rudnytska et al 2021). The present study indicates that SWCNTs at very low quantities significantly down-regulate the expression of numerous microRNAs in the zebrafish embryos in dose-and time-dependent manners.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been shown that very low quantities of SWCNTs may significantly disturb the expression of microRNAs, which participate in the post-transcriptional regulation of most mRNAs and regulate variable physiological and pathophysiological processes in different cells and tissues, including brain tissue (Schratt et al 2006;Agarwal et al 2015;Matamala et al 2018;Wang et al 2018;Goldewski et al 2019;Krichevsky et al 2019;Ma et al 2019;Brennan and Henshall 2020). Previously we have shown that SWCNTs affect the expression of genes encoding enzymes and factors related to immune response, cell proliferation, and cell cycle control as well as some microRNAs in U87 glioma cells and normal human astrocytes (Minchenko et al 2016(Minchenko et al , 2018Rudnytska et al 2021). The present study indicates that SWCNTs at very low quantities significantly down-regulate the expression of numerous microRNAs in the zebrafish embryos in dose-and time-dependent manners.…”
Section: Discussionmentioning
confidence: 93%
“…It has also been shown that the above-mentioned carbon nanotubes may affect the expression of genes encoding important regulatory factors and key enzymes, which control the cell proliferation and apoptosis, such as cyclin D2, parvin beta, dystrobrevin alpha (DTNA), 6-phosphofructo-2-kinase/ fructose-2.6-bisphosphatases-3 (PFKFB3), and PFKFB4, in human U87 glioma cells (Minchenko et al 2016). It is relevant to note that SWCNTs also disturb alternative splicing of pre-mRNA, which we have demonstrated for DTNA, PFKFB3, and PFKFB4 (Minchenko et al 2016). At the same time, detailed mechanisms of this type of carbon nanotubes toxicity are still unidentified and it is possible that they may include signaling pathways of the endoplasmic reticulum stress.…”
mentioning
confidence: 99%
“…Therefore, these carbon nanoparticles affect an immune response, in particular through strong suppression of the expressions of cell surface glycoproteins HLA-DRA (major histocompatibility complex, class II, DR alpha) and HLA-DRB1 and up-regulate the level of microRNAs, that possibly participate in the suppression these mRNA expression ( Minchenko et al, 2018 ). It is intertesting to note that SWCNTs also disturb alternative splicing, particularly 6-phosphofructo-2-kinase/fructose-2.6-bisphosphatase-3 (PFKFB3) and PFKFB4 as well as dystrobrevin alpha (DTNA) pre-mRNA in human U87 glioma cells ( Minchenko et al, 2016b ). Furthermore, carbon nanotubes deregulate the expression of cyclin D2, DUSP1, and lamin B1, which participate in the control of cell cycle and genome stability, as well as many other genes indicating genotoxic effect of these nanoparticles ( Minchenko et al, 2016b , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is intertesting to note that SWCNTs also disturb alternative splicing, particularly 6-phosphofructo-2-kinase/fructose-2.6-bisphosphatase-3 (PFKFB3) and PFKFB4 as well as dystrobrevin alpha (DTNA) pre-mRNA in human U87 glioma cells ( Minchenko et al, 2016b ). Furthermore, carbon nanotubes deregulate the expression of cyclin D2, DUSP1, and lamin B1, which participate in the control of cell cycle and genome stability, as well as many other genes indicating genotoxic effect of these nanoparticles ( Minchenko et al, 2016b , 2018). However, precise mechanisms of single-walled carbon nanotubes toxicity are still largely unknown and seem to include many pathways including endoplasmic reticulum stress signaling pathways like other nanoparticles ( Barberet et al, 2017 , Cao et al, 2017 , Hu et al, 2018 , Simon et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Раніше було показано, що фулерени C 60 і одностінні карбонові нанотрубки впливають на експресію деяких стресчутливих генів, пов'язаних з процесами проліферації клітин, їх виживання та смерті [8,9]. Виявлено зв'язок між стресом ендоплазматичного ретикулуму, який контролює численні процеси, включаючи проліферацію і виживання клітин, та різними захворюваннями, зокрема злоякіс-НАНОТЕХНОЛОГИИ И МЕДИцИНА ними пухлинами і метаболічними захворюваннями [4,5,10].…”
unclassified